Adherence to subcutaneous interferon beta-1a treatment among patients with relapsing multiple sclerosis: the MAIN-MS study - Al-Roughani, Raed; Zakaria, Magd; Cupler, Edward J.; Taha, Karim (Frontiers in Neurology, 2023)
Introduction and Background: Adherence is a critical factor for optimal clinical outcomes in multiple sclerosis (MS) treatment. This study investigated the adherence and clinical outcomes of MS patients treated with subcutaneous (sc) interferon (IFN) beta-1a, an established immunomodulatory treatment for relapsing MS. The benefits of a patient support programme (PSP) were also studied.This Phase-IV prospective, observational multicentre study enrolled patients with relapsing MS who were treated with sc IFN β-1a for 24-months was conducted at 53 centres across 17 countries. The primary endpoint was adherence to sc IFN β-1a treatment as assessed using Morisky Green Levine Medication Adherence Scale (MGLS) scores at month-24. MGLS is a selfreported diagnostic tool to address medication non-adherence, with score ranging from 0 to 4, with 0 representing high adherence, 1-2 representing medium adherence, and 3-4 representing low adherence. Other endpoints included time to study and treatment discontinuation over 24 months, proportion of relapse-free patients and Expanded Disability Status Scale (EDSS) progression (defined as ≥1.0-point increase sustained for 3 months) at Month 24. A subgroup analysis was performed for endpoints based on patients assigned to PSP (yes/no -PSP versus non-PSP subgroup).Results: Of the 577 patients enrolled, 408 had evaluable MGLS scores at Month 24. A total of 336 (58.2%; 95% confidence interval [CI]: 54.1%-62.3%) patients reported high adherence, 57 (9.9%; 95% CI: 7.6%-12.7%) reported medium adherence, and 15 (2.6%; 95% CI: 1.5%-4.3%) reported low adherence at Month 24. The PSP subgroup reported higher adherence (n=206; 65.8%) than the non-PSP subgroup (n=130; 56.5%). By month-24, 52.2% of the patients were relapse-free and 17.2% patients experienced ≥1 relapse. Expanded Disability Status Scale progression was observed in 12.3% of patients. Over the 24-month period, 30.8% patients discontinued treatment, the most common reasons were adverse events (AEs, 10.4%), lost to follow-up (7.1%) and lack of efficacy (5.5%). Overall, 39.6% patients experienced ≥1 AE which were mild-to-moderate.The study demonstrated high adherence to sc IFN β-1a treatment with an added benefit of PSP participation. More than half of the patients remained relapse-free over 24-month period. No new safety concerns to sc IFN β-1a treatment were observed.